Growth of nanocolumnar thin films on patterned substrates at oblique angles. Issue 2 (8th November 2018) - Garcia‐Valenzuela, Aurelio; Muñoz‐Piña, Sandra; Alcala, German; Alvarez, Rafael; Lacroix, Bertrand; Santos, Antonio J.; Cuevas‐Maraver, Jesus; Rico, Victor; Gago, Raul; Vazquez, Luis; Cotrino, Jose; Gonzalez‐Elipe, Agustin R.; et al.
Abstract : The influence of one dimensional substrate patterns on the nanocolumnar growth of thin films deposited by magnetron sputtering at oblique angles is theoretically and experimentally studied. A well‐established growth model has been used to study the interplay between the substrate topography and the thin film morphology. A critical thickness has been defined, below which the columnar growth is modulated by the substrate topography, while for thicknesses above, the impact of substrate features is progressively lost in two stages; first columns grown on taller features take over neighboring ones, and later the film morphology evolves independently of substrate features. These results have been experimentally tested by analyzing the nanocolumnar growth of SiO2 thin films on ion‐induced patterned substrates. Abstract : The influence of substrate patterns on the nanocolumnar growth of SiO2 thin films at oblique angles is studied. A critical thickness has been determined, below which the columnar growth is modulated by the substrate topography. For thicknesses above, pattern height fluctuations are responsible for the appearance of large tilted structures that grow independent of substrate features.